Ghost in the shell, stand alone complex. Solid state society [videorecording (DVD)] - Kamiyama, Kenji; Tanaka, Atsuko; Saka, Osamu, 1930- (Bandai Entertainment, 2007)
In the year 2034, Togusa is the new leader of the team that has increased its personnel; Section 9 has expanded and has to take on a rash of complicated incidents, and investigators find that a hacker nicknamed the Puppetmaster is behind them.